Analisis Penjualan Produk Soju Halal Berdasarkan Perspektif Hukum Ekonomi Islam di Indonesia - Permata, Karina; Karunia, Karunia; Ayu Lestari, Megha; Yolanda Azahra, Serla (Sharia Journal and Education Center Publishing, 2024)
Abstract The influence of the Korean Wave on the food and beverage industry in Indonesia has brought the consumption trend of Halal Soju to the Indonesian people. Through a qualitative approach, this study explores how the Korean Wave has influenced the consumption trends of Indonesians, especially in terms of the food and beverage industry. This research shows that Halal Soju, as a product following the Korean Wave trend, is controversial in the context of Islamic law due to its similarity to alcoholic Soju. MUI's fatwa and Islamic economic principles are used to assert that the consumption of Halal Soju is not in accordance with religious teachings and the principles of Islamic business. Through secondary data collection from Islamic legal literature and primary sources, this research provides a detailed overview of the legal and religious implications regarding the consumption of Halal Soju in Indonesia. The results show the need for awareness of halal products and a deeper understanding of the principles of Islamic law in the context of the food and beverage industry which is influenced by global phenomena such as the Korean Wave. Keywords: Halal Soju, Business, Law Abstrak Pengaruh Korean Wave terhadap industri makanan dan minuman di Indonesia membawa tren konsumsi Soju Halal kepada masyarakat Indonesia. Melalui pendekatan kualitatif, penelitian ini mengeksplorasi bagaimana Korean Wave memengaruhi tren konsumsi masyarakat Indonesia, terutama dalam hal industri makanan dan minuman. Penelitian ini menunjukkan bahwa Soju Halal, sebagai produk yang mengikuti tren Korean Wave, menjadi kontroversial dalam konteks hukum Islam karena kemiripannya dengan Soju beralkohol. Fatwa MUI dan prinsip ekonomi Islam digunakan untuk menegaskan bahwa konsumsi Soju Halal tidak sesuai dengan ajaran agama dan prinsip jual beli yang sah. Melalui pengumpulan data sekunder dari literatur hukum Islam dan sumber-sumber primer, penelitian ini memberikan gambaran yang mendetail tentang implikasi hukum dan keagamaan terkait konsumsi Soju Halal di Indonesia. Hasilnya menunjukkan perlunya kesadaran akan kehalalan produk serta pemahaman yang lebih dalam terhadap prinsip hukum Islam dalam konteks industri makanan dan minuman yang dipengaruhi oleh fenomena global seperti Korean Wave. Kata Kunci: Soju Halal, Jual Beli, Hukum